Due to an image crisis, now - Soares, Nicolas Oliveira (Farol, 2024)
This text focuses on the relationship between image, culture and identity, by elaborating on the ways in which the image influences the construction of social imaginaries and how it can support or oppose power structures. In this way, it challenges the narrative of the idealized image, which often excludes subalternized and racialized subjects. It reinforces the provocation to contest and interrupt the structures of representation that regulate bodies and subjectivities, reaffirming the need for a decolonial take on culture and history. The text seeks to review the complexity of representation, confronting the images that regulate bodies and subjectivities, while exploring the dissimilarity and cultural stigmas associated with them.